Deciphering popular routes in urban parks: The impact of environmental factors on the amount, intensity and diversity of physical activity - Li, Jie; Ma, Haoran; Kwan, Mei-Po; Zhang, Shaojie (Urban forestry & urban greening, 2025)
Urban parks play a crucial role in human health and well-being, such as promoting physical activity (PA). However, past studies on park-based PA often overlooked other PA characteristics beyond the amount of PA. To bridge this gap, we explored what environmental factors are significantly associated with PA amount, intensity, and diversity, utilizing PA trajectory data collected from the Keep application, which includes walking, jogging, and cycling, with Nanjing as a case study. We employed hierarchical linear models (HLMs) to examine the associations between environmental features and PA at two nested levels: the route level (environmental factors along routes) and the park level (environmental factors of parks and neighborhoods). The results showed that: (1) PA intensity significantly increased on exercise routes located along park boundary trails or shaped as loops. (2) Blue space density emerged as the most essential landscape feature in explaining overall PA amount, while the Normalized Difference Vegetation Index (NDVI) showed a negative association with PA amount. (3) Linear and sports parks were associated with higher PA intensity, while specialized and nature parks were associated with greater PA diversity compared to comprehensive parks. (4) The density of transit stops around parks was positively associated with PA amount and diversity and population density was positively associated with PA intensity, while Services and Facilities Points Of Interest (SFPOI) negatively affected PA amount and intensity. Based on these findings, we recommend strategies for urban fitness trail planning and infrastructure allocation to support the nuanced park environmental management. These proposals aim to increase park utilization for PA and promote urban public health and well-being.